Carbon Dioxide Laser Guidelines - Krupa Shankar, DS (Medknow Publications, 2009)
The carbon dioxide (CO(2)) laser is a versatile tool that has applications in ablative lasing and caters to the needs of routine dermatological practice as well as the aesthetic, cosmetic and rejuvenation segments. This article details the basics of the laser physics as applicable to the CO(2) laser and offers guidelines for use in many of the above indications.